The Results of a Complex Analysis of the Modified Pratt-Yaskorskiy Performance Metrics Based on the Two-Dimensional Markov-Renewal-Process; Lecture Notes in Computer Science; Vol. 9875 : Computational Collective Intelligence. Pt.1 - Geringer V. E. Viktor Evgenjevich (2016, 2016)
Title screen